HUBUNGAN INDEKS MASSA TUBUH (IMT) DENGAN STATUS KOGNITIF PADA LANSIA DI KELURAHAN TANJUNG BUNTUNG WILAYAH KERJA PUSKESMAS TANJUNG BUNTUNG KOTA BATAM TAHUN 2022 - Natallian, Zolla; Roza, Nelli; Eltrikanawati, T. (Jurnal Sains, Teknologi dan Kesehatan, 2023)
One of the main problems faced by the elderly is the deterioration of cognitive function which is a degenerative disease. According to the World Health Organization in 2021, there are more than 55 million elderly people worldwide who experience dementia and impaired cognitive function. According to data on elderly morbidity in Batam city, ten elderly health problems in Batam city include cognitive impairment as many as 30,693 cases and Body Mass Index (BMI) as many as 24,334 cases. The purpose of this study was to determine the relationship between Body Mass Index (BMI) and cognitive status in the elderly. This type of research is observative analytic using cross sectional method on 64 elderly people selected based on cluster random sampling. The research was conducted in Tanjung Buntung Village, Tanjung Buntung Health Center, Batam City. The results of this study showed that 51.6% of the elderly in Tanjung Buntung Village experienced cognitive decline and as many as 62.5% of the elderly had a low Body Mass Index (BMI). Based on the chi-square statistical test obtained p = 0.005 <0.05, meaning that there is a significant relationship between Body Mass Index (BMI) and Cognitive Status in the elderly in Tanjung Buntung Village. The Head of Puskesmas Tanjung Buntung is expected to be able to make an elderly health program about counseling regarding cognitive impairment in the elderly and take regular measurements of Body Mass Index to the elderly in the Tanjung Buntung health centre.